2021
DOI: 10.1111/coa.13869
|View full text |Cite|
|
Sign up to set email alerts
|

Acute paediatric mastoiditis in the UK before and during the COVID‐19 pandemic: A national observational study

Abstract: Objectives To explore the impact of COVID‐19 on the management and outcomes of acute paediatric mastoiditis across the UK. Design National retrospective and prospective audit. Setting 48 UK secondary care ENT departments. Participants Consecutive children aged 18 years or under, referred to ENT with a clinical diagnosis of mastoiditis. Main outcome measures Cases were divided into Period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
1
7
0
2
Order By: Relevance
“…10 We predicted delayed, more severe presentations 17 and microbial alterations similar to other common infectious ENT conditions such as otitis media, and mastoiditis during this era. 9,11 Surprisingly, clinical features at presentation were not significantly different apart from increased CRP levels. In contrast to our findings, Callego et al's report on peritonsillar infections during the COVID 19 era in Spain reported more delayed, severe presentations and prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…10 We predicted delayed, more severe presentations 17 and microbial alterations similar to other common infectious ENT conditions such as otitis media, and mastoiditis during this era. 9,11 Surprisingly, clinical features at presentation were not significantly different apart from increased CRP levels. In contrast to our findings, Callego et al's report on peritonsillar infections during the COVID 19 era in Spain reported more delayed, severe presentations and prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 88%
“…Prompt treatment is necessary, as PTA may give rise, albeit rarely, to life-threatening complications secondary to spread along fascial planes to the deep neck and chest. [6][7][8] The COVID-19 pandemic has been shown to impact the microbiology 9 and clinical course of several paediatric ENT infectious diseases, including otitis media, sinusitis, laryngitis and mastoiditis. [10][11][12] Acute mastoiditis demonstrated reductions in common pathogens such as Streptococcus pneumoniae and Haemophilus influenzae, with a concomitant increase in Pseudomonas cultivation during the COVID era.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a national UK observation study of acute paediatric mastoiditis during COVID‐19 showed only one positive patient (0.9%). 13 This suggests a low risk of otological complications from AOM in COVID‐19 patients.…”
Section: Discussionmentioning
confidence: 94%
“…24,25 However, if indeed the avoidance of medical counseling was the main factor, one would expect a substantial parallel decrease in UTI burden as well, which was not the case; (4) The higher rate of complications during the first COVID year, especially acute mastoiditis (0.5% vs. 0.3% in pre-COVID years, P < 0.001), does not coincide with recent UK data. 26 This could be explained by a decrease in the total AOM episodes, therefore not reflecting a truly increased incidence of acute mastoiditis. Another explanation can be attributed to a higher threshold of seeking medical care during the first COVID period, leading to a selection bias.…”
Section: Discussionmentioning
confidence: 99%